Aluminum alloy plate for can body

JP7636311B2Active Publication Date: 2025-02-26KOBE STEEL LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021163590
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-04
Publication Date
2025-02-26
Estimated Expiration
2041-10-04

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、成形される絞りカップの開口部における肉厚の周方向の異方性が低減される缶胴用アルミニウム合金板を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636311000001
    Figure 0007636311000001
  • Figure 0007636311000002
    Figure 0007636311000002
Patent Text Reader

Abstract

To provide an aluminum alloy sheet for can bodies that has reduced circumferential anisotropy in the wall thickness of the opening of a drawing cup to be molded.SOLUTION: An aluminum alloy sheet for can bodies contains Si: 0.16 mass% or more and 0.60 mass% or less, Fe: 0.3 mass% or more and 0.6 mass% or less, Cu: 0.10 mass% or more and 0.35 mass% or less, Mn: 0.5 mass% or more and 1.2 mass% or less, Mg: 0.7 mass% or more and 2.0 mass% or less, with the balance being Al and inevitable impurities. When the aluminum alloy sheet for can bodies is subjected to a structural observation, the number density of intermetallic compounds with a circle equivalent diameter of 0.10 μm or more and less than 1.00 μm is 1.7×105 / mm2 or more to 4.0×105 / mm2, and the number density of intermetallic compounds equal to or greater than a critical circle equivalent diameter to be the core of recrystallization is 1.0×103 / mm2 or more to 3.5×103 / mm2 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy sheet for can bodies. [Background technology]

[0002] The body of an aluminum beverage can is manufactured through processes such as drawing, redrawing, ironing, washing and drying, external printing and baking, internal painting and baking, and necking (mouth narrowing). The sidewall of the cup (drawn cup) after drawing and redrawing becomes thicker from the bottom to the opening compared to the plate thickness before processing. In this case, the degree of thickening varies in the circumferential direction due to the plastic anisotropy of the material, and as a result, a cup may be manufactured with a different wall thickness in the circumferential direction at the same height. If the wall thickness of the cup after drawing and redrawing is uneven in the circumferential direction, when the wall thickness is processed to a uniform thickness in the circumferential direction in the subsequent ironing process, the processing rate differs in the circumferential direction, so the tensile stress generated in the sidewall becomes uneven in the circumferential direction, making it more likely to break during processing. In recent years, there has been a trend toward can bodies with smaller body diameters than before, in other words, can bodies with a larger drawing ratio. As the drawing ratio increases, the wall thickness difference in the circumferential direction of the cup also tends to increase, so there is a possibility that the problem of ironing workability will become more apparent.

[0003] In relation to the above, a method for producing an aluminum alloy sheet for a can body having good roundness of a drawn cup has been proposed, which specifies the chemical composition, ear ratio, soaking conditions, hot rough rolling conditions, hot finish rolling conditions, and cold rolling conditions (see, for example, Patent Document 1). Also, a method for producing an aluminum alloy sheet capable of improving ironing formability has been proposed, which specifies the chemical composition, soaking conditions, hot rough rolling conditions, hot finish rolling conditions, cold rolling conditions, finish annealing conditions, and average crystal grain size of the hot rolled sheet (see, for example, Patent Document 2). Furthermore, a method for producing an aluminum alloy sheet for a DI can body having excellent high-speed ironing formability has been proposed, which specifies the chemical composition, soaking conditions, hot rough rolling conditions, hot finish rolling conditions, intermediate annealing conditions, cold rolling conditions, and finish annealing conditions (see, for example, Patent Document 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-235475 A [Patent Document 2] JP 2006-207006 A [Patent Document 3] Japanese Patent Application Publication No. 10-121177 Summary of the Invention [Problem to be solved by the invention]

[0005] However, no prior art is known that focuses on the sidewall thickness of the drawn cup, and further on the difference in wall thickness in the circumferential direction (anisotropy). In addition, there is a demand to ensure the ironing workability of can bodies with large drawing ratios, which have been increasing in recent years.

[0006] An object of the present invention is to provide an aluminum alloy sheet for a can body in which the circumferential anisotropy of the wall thickness at the opening of a formed drawn cup is reduced. [Means for solving the problem]

[0007] The aluminum alloy sheet for can bodies according to the present invention contains Si: 0.16% by mass or more and 0.60% by mass or less, Fe: 0.3% by mass or more and 0.6% by mass or less, Cu: 0.10% by mass or more and 0.35% by mass or less, Mn: 0.5% by mass or more and 1.2% by mass or less, Mg: 0.7% by mass or more and 2.0% by mass or less, and the balance being Al and unavoidable impurities. In the structure observation of the aluminum alloy sheet for can bodies, the number density of intermetallic compounds having a circle equivalent diameter of 0.10 μm or more and less than 1.00 μm is 1.7×10 5 pieces / mm 2 Above 4.0×10 5 pieces / mm 2 The number density of intermetallic compounds with a diameter equal to or larger than the critical circle equivalent diameter that becomes the nucleus of recrystallization is 1.0×10 3 pieces / mm 2 More than 3.5 x 10 3 pieces / mm2 The following is the result. Effect of the Invention

[0008] According to the present invention, it is possible to provide an aluminum alloy sheet for a can body in which the circumferential anisotropy of the wall thickness at the opening of a formed drawn cup is reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In this specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. Furthermore, the content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. Furthermore, the upper and lower limits of the numerical ranges described in this specification can be arbitrarily selected and combined from the numerical values ​​exemplified as the numerical ranges. Hereinafter, the embodiments of the present invention will be described in detail. However, the embodiments shown below are examples of aluminum alloy sheets for can bodies to embody the technical idea of ​​the present invention, and the present invention is not limited to the aluminum alloy sheets for can bodies shown below.

[0010] Aluminum alloy plate for can body The aluminum alloy sheet for can bodies according to one embodiment of the present invention is made of, for example, an Al-Mn-Mg based alloy, an Al-Mg-Mn based alloy, etc. Examples of the Al-Mn-Mg based alloy, an Al-Mg-Mn based alloy, etc. include general JIS alloys such as 3004 and 3104.

[0011] Specifically, the aluminum alloy sheet for can bodies contains Si: 0.16% by mass to 0.60% by mass, Fe: 0.3% by mass to 0.6% by mass, Cu: 0.10% by mass to 0.35% by mass, Mn: 0.5% by mass to 1.2% by mass, Mg: 0.7% by mass to 2.0% by mass, and the balance being Al and unavoidable impurities. In the structure observation of the aluminum alloy sheet for can bodies, the number density of intermetallic compounds having a circle equivalent diameter of 0.10 μm or more and less than 1.00 μm is 1.7×105 pieces / mm 2 Above 4.0×10 5 pieces / mm 2 The number density of intermetallic compounds with a diameter equal to or larger than the critical circle equivalent diameter that becomes the nucleus of recrystallization is 1.0×10 3 pieces / mm 2 More than 3.5×10 3 pieces / mm 2 The following is the result.

[0012] The aluminum alloy sheet for the can body contains Si, Fe, Cu, Mn, and Mg in a predetermined range, and the number density of the intermetallic compounds having a circle equivalent diameter in a predetermined range in the structure observation and the number density of the intermetallic compounds serving as the nuclei of recrystallization are each within a predetermined range, so that the anisotropy of the circumferential thickness at the opening of the drawn cup to be formed is reduced. This is considered to be because, for example, the Cube orientation density, which affects the circumferential thickness difference of the drawn cup, is appropriately controlled, so that the circumferential thickness difference of the drawn cup is reduced. Specifically, for example, the Cube orientation density has a large effect on the circumferential thickness distribution of the side wall thickness of the drawn cup. For example, when the Cube orientation density is small, the drawn cup side wall is thin in the 45° direction with respect to the rolling direction and thick in the 90° direction, so that the circumferential thickness difference is large. Also, when the Cube orientation density is large, the drawn cup side wall is thin in the 0° direction with respect to the rolling direction, so that the circumferential thickness difference is large. Furthermore, by adjusting the Si content within a predetermined range, the number density of intermetallic compounds having a circle equivalent diameter within a predetermined range and the number density of intermetallic compounds having a circle equivalent diameter that serves as a nucleus for recrystallization are set within predetermined ranges, thereby achieving an appropriate Cube orientation density and reducing the circumferential thickness difference in the side wall of the drawn cup.

[0013] The contents of the various components contained in the aluminum alloy sheet for can bodies and the reasons for limiting the contents will be described below.

[0014] Si: 0.16 mass% or more and 0.60 mass% or less When the Si content is less than 0.16 mass%, the number density of intermetallic compounds having a circle equivalent diameter of 0.10 μm or more and less than 1.00 μm becomes small, so the cube orientation density becomes small, and the side wall thickness in the 45° direction and the 90° direction of the produced drawn cup becomes thin and the wall thickness difference in the circumferential direction of the drawn cup becomes large. When the Si content exceeds 0.60 mass%, the number density of intermetallic compounds having a circle equivalent diameter of 0.10 μm or more and less than 1.00 μm becomes large, so the cube orientation density becomes large, and the side wall thickness in the 0° direction of the produced drawn cup becomes thin and the wall thickness difference in the circumferential direction of the drawn cup becomes large. The lower limit of the Si content is preferably 0.18 mass% or more, more preferably 0.20 mass% or more, even more preferably 0.24 mass% or more, and particularly preferably 0.3 mass% or more. The upper limit of the Si content may be preferably 0.56 mass % or less, more preferably 0.54 mass % or less, and further preferably 0.50 mass % or less.

[0015] Fe: 0.3% by mass or more and 0.6% by mass or less If the Fe content is less than 0.3 mass%, the intermetallic compounds (e.g., Al-Fe-Mn intermetallic compounds) are insufficient, and surface defects (seizure) may occur on the side wall during ironing. If the Fe content exceeds 0.6 mass%, the amount of large-sized intermetallic compounds increases, and fracture may occur during ironing. The lower limit of the Fe content is preferably 0.34 mass% or more, more preferably 0.36 mass% or more, and even more preferably 0.38 mass% or more. The upper limit of the Fe content is preferably 0.55 mass% or less, more preferably 0.5 mass% or less, and even more preferably 0.46 mass% or less.

[0016] Cu: 0.10 mass% or more and 0.35 mass% or less If the Cu content is less than 0.10% by mass, the strength (post-baking yield strength) is insufficient, and the pressure resistance of the can is insufficient. If the Cu content exceeds 0.35% by mass, the strength becomes too high and the formability may decrease. The lower limit of the Cu content is preferably 0.14% by mass or more, more preferably 0.16% by mass or more, and even more preferably 0.18% by mass or more. The upper limit of the Cu content is preferably 0.33% by mass or less, more preferably 0.30% by mass or less, and even more preferably 0.26% by mass or less.

[0017] Mn: 0.5% by mass or more and 1.2% by mass or less If the Mn content is less than 0.5% by mass, the strength (post-baking yield strength) is insufficient, and the pressure resistance of the can is insufficient. If it exceeds 1.2% by mass, the amount of large-sized intermetallic compounds increases, and breakage may occur during ironing. The lower limit of the Mn content is preferably 0.6% by mass or more, more preferably 0.8% by mass or more, and even more preferably 0.9% by mass or more. The upper limit of the Mn content is preferably 1.15% by mass or less, more preferably 1.10% by mass or less, even more preferably 1.08% by mass or less, and particularly preferably 1.06% by mass or less.

[0018] Mg: 0.7% by mass or more and 2.0% by mass or less If the Mg content is less than 0.7% by mass, the strength (post-baking yield strength) is insufficient, and the pressure resistance of the can is insufficient. If it exceeds 2.0% by mass, the strength becomes too high and formability may decrease. The lower limit of the Mg content is preferably 0.8% by mass or more, more preferably 0.9% by mass or more, and even more preferably 0.94% by mass or more. The upper limit of the Mg content is preferably 1.6% by mass or less, more preferably 1.4% by mass or less, and even more preferably 1.35% by mass or less.

[0019] Cr: 0.01 mass% or more and 0.10 mass% or less As is generally known, the aluminum alloy sheet may contain Cr. A Cr content of 0.01% by mass or more contributes to improving the strength of the material. Furthermore, if the Cr content is 0.10% by mass or less, it does not affect the material properties of the aluminum alloy sheet and the can properties after ironing. If the Cr content is 0.10% by mass or less, the generation of coarse intermetallic compounds is suppressed, and the deterioration of formability during ironing is suppressed. The upper limit of the Cr content may be preferably 0.05% by mass or less, or 0.03% by mass or less.

[0020] Zn: 0.01 mass% or more and 0.40 mass% or less As is generally known, the aluminum alloy sheet may contain Zn. If the content of Zn is 0.40 mass% or less, it does not significantly affect the material properties of the aluminum alloy sheet and the can properties after ironing. Although Zn is an inevitable impurity, Zn can be actively added within the above range. The upper limit of the Zn content is preferably 0.30 mass% or less, more preferably 0.26 mass% or less, more preferably 0.24 mass% or less, and even more preferably 0.20 mass% or less. The lower limit of the Zn content may be, for example, 0.01 mass% or more, preferably 0.10 mass% or more, and more preferably 0.16 mass% or more.

[0021] Ti: 0.005 mass% or more and 0.100 mass% or less As is generally known, the aluminum alloy plate may contain Ti. Ti is added as necessary for the purpose of refining the ingot crystal grains. Refining the ingot structure during casting improves castability and enables high-speed casting. This effect is obtained by adding 0.005% by mass or more. On the other hand, if the Ti content is 0.100% by mass or less, the generation of coarse intermetallic compounds can be suppressed. In addition, when Ti is added, for example, an ingot refiner (Al-Ti-B) may be added to the molten metal before casting. In this case, for example, if the mass ratio of Ti to B is 5:1, B is inevitably added according to the content ratio, but this does not affect the characteristics. The upper limit of the Ti content is preferably 0.080% by mass or less, more preferably 0.060% by mass or less, and even more preferably 0.040% by mass or less. In addition, the lower limit of the Ti content may be, for example, 0.005% by mass or more.

[0022] The total content of Cr and Ti is 0.01% or more and 0.150% or less by mass. When the total content of Cr and Ti is 0.150 mass% or less, the generation of coarse intermetallic compounds is suppressed, and the deterioration of formability is suppressed. As long as the content of Cr and Ti does not exceed the upper limit value, not only when the aluminum alloy contains one or more kinds, i.e., only one kind, but also when the aluminum alloy contains two or more kinds, the effect of the present invention is naturally suppressed from being hindered.

[0023] (balance: Al and unavoidable impurities) The aluminum alloy sheet for can bodies may contain inevitable impurities in addition to Al and the above alloy components. Examples of inevitable impurities include V, Na, Zr, Ni, Ca, In, Sn, and Ga. The upper limit of the allowable content of inevitable impurities for Zr may be, for example, 0.3 mass% or less, preferably 0.1 mass% or less, and more preferably 0.05 mass% or less. For elements other than Zr, the content may be, for example, 0.05 mass% or less for each element and 0.15 mass% or less in total. If the content is within the above range, the effects of the present invention are suppressed from being hindered not only when the elements are contained as inevitable impurities, but also when the elements are added.

[0024] Number density of intermetallic compounds with a circle equivalent diameter of 0.10 μm or more and less than 1.00 μm: 1.7 × 10 5 / mm 2 pcs or more 4.0×10 5 pieces / mm 2 below The number density of intermetallic compounds having a circle-equivalent diameter of 0.10 μm or more and less than 1.00 μm is calculated by observing the structure of a cross section parallel to the rolling direction of an aluminum alloy sheet as a backscattered electron composition (COMPO) image. Specifically, the area of ​​each intermetallic compound (e.g., Al-Fe-Mn, Al-Fe-Mn-Si, etc.) identified from the COMPO image is measured, and the number density of the intermetallic compounds is calculated as the number of intermetallic compounds per unit area having a circle-equivalent diameter of 0.10 μm or more and less than 1.00 μm calculated from the area.

[0025] The number density of intermetallic compounds with a circle equivalent diameter in a specified range is 1.7×10 5 pieces / mm 2 If the ratio is less than 4.0×10, the cube orientation density is decreased during recrystallization, and the side wall thickness in the 45° direction relative to the rolling direction of the produced drawn cup is thin and the side wall thickness in the 90° direction is thick, resulting in a large difference in the circumferential thickness of the drawn cup. 5 pieces / mm 2 If the number density exceeds 1.8×10, the density of the cube orientation increases during recrystallization, and the side wall thickness in the 0° direction with respect to the rolling direction becomes thin in the produced drawn cup, resulting in a large difference in the circumferential thickness of the drawn cup. The lower limit of the number density of the intermetallic compounds having a circle equivalent diameter in the specified range is preferably 1.8×10 5 pieces / mm 2 More preferably, it is 1.85×10 5 pieces / mm 2 The upper limit of the number density of the intermetallic compounds having a circle equivalent diameter in the predetermined range is preferably 3.8×10 5 pieces / mm 2 More preferably, it is 3.6×10 or less. 5 pieces / mm 2 More preferably, it is 3.2×10 5 pieces / mm 2It may be the following:

[0026] Number density of intermetallic compounds with a diameter equal to or larger than the critical circle equivalent diameter that become the nuclei of recrystallization: 1.0×10 3 pieces / mm 2 More than 3.5 x 10 3 pieces / mm 2 below The critical diameter η of the recrystallization nucleus PSN is calculated by the following formula (see, for example, HE Vatne, O. Engler, E. Nes: Materials Science and Technology, February, 1997, Vol. 13, pp. 93-102.) using the area fraction f of intermetallic compounds having a circle-equivalent diameter of 0.10 μm or more and less than 1.00 μm and the average radius r measured from the above COMPO image. η PSN =(4 / 3) / (10 6 -(3f / 2r)) It is said that when recrystallization occurs using compounds having a diameter equal to or larger than the critical circle equivalent diameter as nuclei, the crystal orientation of the recrystallized grains becomes random.

[0027] The critical circle equivalent diameter of the intermetallic compound which becomes the nucleus of recrystallization of the aluminum alloy sheet for the can body may be, for example, more than 1.48 μm and not more than 1.80 μm. The lower limit of the critical circle equivalent diameter of the intermetallic compound may be preferably 1.49 μm or more. The upper limit of the critical circle equivalent diameter of the intermetallic compound may be preferably 1.70 μm or less, more preferably 1.68 μm or less.

[0028] The number density of intermetallic compounds with a diameter equal to or larger than the critical circle equivalent diameter that becomes the nucleus of recrystallization is 1.0×10 3 pieces / mm 2 If the ratio is less than 3.5×10, the density of cube orientation increases during recrystallization, and the side wall thickness in the 0° direction with respect to the rolling direction becomes thin in the produced drawn cup, resulting in a large difference in the circumferential thickness of the drawn cup. 3 pieces / mm 2If the number density exceeds 1.6×10, the density of the cube orientation will be small during recrystallization, and the side wall thickness in the 45° direction to the rolling direction will be thin and the side wall thickness in the 90° direction will be thick in the produced drawn cup, resulting in a large difference in the circumferential thickness of the drawn cup. 3 pieces / mm 2 More preferably, it is 2.0×10 3 pieces / mm 2 The upper limit of the number density of intermetallic compounds having a diameter equal to or larger than the critical circle diameter is preferably 3.2×10 3 pieces / mm 2 It may be the following:

[0029] In a drawn cup formed from an aluminum alloy plate for a can body, the variation in circumferential thickness near the opening is suppressed. The variation in circumferential thickness can be evaluated by circumferential anisotropy (%), which is calculated as a percentage by subtracting the maximum value from the minimum value of the wall thickness measured in the circumferential direction and dividing the result by the average value of the wall thickness in the circumferential direction. The upper limit of the circumferential anisotropy may be, for example, 10.8% or less, and preferably 10.7% or less. The lower limit of the circumferential anisotropy is 0%.

[0030] Manufacturing method An example of a method for producing an aluminum alloy sheet for a can body will be described below. The method for producing an aluminum alloy sheet for a can body includes a casting step as a first step, a homogenization heat treatment step as a second step, a hot rolling step as a third step, and a cold rolling step as a fourth step, which are carried out in this order.

[0031] From the 1st process to the 2nd process: Casting process, homogenization heat treatment process The first step is to produce an ingot having a target composition by a semi-continuous casting method, and the second step is to perform a homogenization heat treatment on the aluminum alloy ingot produced in the first step.

[0032] In the first step, an aluminum alloy is cast by a semi-continuous casting method (DC (direct chill) casting) to obtain an ingot. Next, in the second step, the ingot surface layer is subjected to facing and homogenization heat treatment in the region that will become a non-uniform structure. In the homogenization heat treatment, it is preferable to hold the ingot at a temperature of about 480°C to 600°C for 2 hours or more. After the homogenization heat treatment is completed, the ingot may be cooled to the hot rolling start temperature and hot rolling, which is the third step, may be started, or the ingot may be cooled once to a temperature of 200°C or less including room temperature, and then reheated to the hot rolling start temperature before starting hot rolling. In addition, facing may be performed before the homogenization heat treatment, or may be performed when the ingot surface is cooled to a temperature of 200°C or less including room temperature after the homogenization heat treatment.

[0033] 3rd process: Hot rolling process The third step is hot rolling the aluminum alloy ingot that has been subjected to the homogenization heat treatment in the second step. The thickness of the hot-rolled plate obtained by hot rolling is usually set by calculating backward the total rolling reduction ratio by cold rolling from the thickness of the product plate obtained by cold rolling.

[0034] The start temperature of hot rolling may be, for example, 450°C or higher, preferably 480°C or higher. The lower limit of the coiling temperature, which is the end temperature of hot rolling, may be, for example, 300°C or higher, preferably 330°C or higher, and more preferably 340°C or higher. The upper limit of the coiling temperature may be, for example, 370°C or lower, preferably 360°C or lower. When the coiling temperature is 370°C or lower, the occurrence of a surface defect called seizure on the surface of the hot rolled plate is suppressed, and the properties of the plate surface are improved.

[0035] 4th process: Cold rolling process The fourth step is a step of cold rolling the hot-rolled sheet hot-rolled in the third step. The fourth step may include a first cold rolling step, a first intermediate annealing step, a second cold rolling step, a second intermediate annealing step, and a final cold rolling step.

[0036] In the first cold rolling step, the hot rolled sheet after hot rolling is cold rolled to a predetermined sheet thickness. The processing rate (rolling rate) in the first cold rolling step is preferably 40% or more. If the processing rate is 40% or more, the cube orientation density is prevented from becoming small during recrystallization. As a result, in the formed drawn cup, the side wall thickness in the 45° direction with respect to the rolling direction is prevented from becoming thin, and the side wall thickness in the 90° direction is prevented from becoming thick, so that the wall thickness difference in the circumferential direction of the drawn cup is prevented from becoming large. The lower limit of the processing rate in the first cold rolling step is preferably 50% or more, more preferably 60% or more, and further preferably 70% or more.

[0037] In the first intermediate annealing step, the first cold rolled sheet is subjected to intermediate annealing. The annealing temperature is preferably set within a range of 250°C to 290°C. Within this range, the cube orientation density is prevented from decreasing during recrystallization. As a result, in the formed drawn cup, the side wall thickness in the 45° direction with respect to the rolling direction is prevented from becoming thin, and the side wall thickness in the 90° direction is prevented from becoming thick, so that the wall thickness difference in the circumferential direction of the drawn cup is prevented from increasing. The lower limit of the annealing temperature in the first intermediate annealing step may be preferably 260°C or higher. The upper limit of the annealing temperature in the first intermediate annealing step may be preferably 280°C or lower. It is believed that by performing the first intermediate annealing step at a predetermined annealing temperature, the cube orientation density is improved in the second intermediate annealing step described later.

[0038] In the first intermediate annealing step, the first cold rolled sheet may be heated to the annealing temperature at a temperature increase rate of 30° C. / hour or more and 50° C. / hour or less. The lower limit of the temperature increase rate may be preferably 35° C. / hour or more. The upper limit of the temperature increase rate may be preferably 45° C. / hour or less. The time for holding the annealing temperature may be, for example, 2 hours or more and 6 hours or less. The lower limit of the time for holding the annealing temperature may be preferably 3 hours or more. The upper limit of the time for holding the annealing temperature may be preferably 5 hours or less. After holding the annealing temperature, the sheet may be cooled to a predetermined cooling temperature at a temperature decrease rate of, for example, 30° C. / hour or more and 50° C. / hour or less. The lower limit of the temperature decrease rate may be preferably 35° C. / hour or more. The upper limit of the temperature decrease rate may be preferably 45° C. / hour or less. The cooling temperature may be, for example, 220° C. or less, preferably 210° C. or less.

[0039] In the second cold rolling process, the first cold rolled sheet after the first intermediate annealing is cold rolled to a predetermined sheet thickness. The processing rate (rolling rate) of the second cold rolling process is preferably 20% or less. If the processing rate is 20% or less, the cube orientation density is prevented from becoming small during recrystallization. As a result, in the formed drawn cup, the side wall thickness in the 45° direction with respect to the rolling direction is prevented from becoming thin, and the side wall thickness in the 90° direction is prevented from becoming thick, so that the wall thickness difference in the circumferential direction of the drawn cup is prevented from becoming large. The upper limit of the processing rate of the second cold rolling process may be preferably 18% or less, more preferably 16% or less, and even more preferably 14% or less. The lower limit of the processing rate of the second cold rolling process may be, for example, 5% or more.

[0040] In a manufacturing method of an aluminum alloy sheet for a can body, if the first intermediate annealing step and the second cold rolling step are not performed, the cube orientation density is not sufficiently large in the subsequent second intermediate annealing step, and as a result, the sidewall thickness in the 45° direction to the rolling direction of the formed drawn cup becomes thin and the sidewall thickness in the 90° direction becomes thick, resulting in a large difference in thickness in the circumferential direction of the drawn cup.

[0041] In the second intermediate annealing step, the second cold rolled sheet is subjected to intermediate annealing. The annealing temperature at this time is preferably in the range of 300°C to 450°C. Within this range, the cube orientation density is suppressed from becoming small during recrystallization. As a result, in the formed drawn cup, the side wall thickness in the 45° direction with respect to the rolling direction is suppressed from becoming thin, and the side wall thickness in the 90° direction is suppressed from becoming thick, so that the wall thickness difference in the circumferential direction of the drawn cup is suppressed from becoming large. The lower limit of the annealing temperature in the second intermediate annealing step may be preferably 300°C or more, more preferably 320°C or more. The upper limit of the annealing temperature in the second intermediate annealing step may be preferably 400°C or less, more preferably 380°C or less.

[0042] In the second intermediate annealing step, the second cold rolled sheet may be heated to the annealing temperature at a temperature increase rate of 30° C. / hour or more and 50° C. / hour or less. The lower limit of the temperature increase rate may be preferably 35° C. / hour or more. The upper limit of the temperature increase rate may be preferably 45° C. / hour or less. The time for holding the annealing temperature may be, for example, 2 hours or more and 6 hours or less. The lower limit of the time for holding the annealing temperature may be preferably 3 hours or more. The upper limit of the time for holding the annealing temperature may be preferably 5 hours or less. After holding the annealing temperature, the sheet may be cooled to a predetermined cooling temperature at a temperature decrease rate of, for example, 30° C. / hour or more and 50° C. / hour or less. The lower limit of the temperature decrease rate may be preferably 35° C. / hour or more. The upper limit of the temperature decrease rate may be preferably 45° C. / hour or less. The cooling temperature may be, for example, 240° C. or less, preferably 210° C. or less.

[0043] In the final cold rolling process, the secondary cold rolled sheet after the secondary intermediate annealing is cold rolled to a predetermined sheet thickness. The working ratio in the final cold rolling process is preferably 80% or more and 95% or less. When the working ratio is 80% or more, the strength of the aluminum alloy sheet is sufficient, and the pressure resistance of the can after DI forming and baking is sufficient. In addition, the cube orientation density after the final cold rolling process is prevented from becoming too large, and in the formed drawn cup, the side wall thickness in the 0° direction with respect to the rolling direction is prevented from becoming thin, and the wall thickness difference in the circumferential direction of the drawn cup is reduced. In addition, when the working ratio is 95% or less, the strength of the aluminum alloy sheet is prevented from becoming too large, and the deterioration of formability is prevented. In addition, the cube orientation density after the final cold rolling process is prevented from becoming too small, and the sidewall thickness in the 45° direction with respect to the rolling direction of the formed drawn cup is prevented from becoming thin, and the sidewall thickness in the 90° direction is prevented from becoming thick, so that the wall thickness difference in the circumferential direction of the drawn cup is prevented from becoming large. The lower limit of the processing rate in the final cold rolling process may be preferably 85% or more. The upper limit of the processing rate in the final cold rolling process may be preferably 90% or less.

[0044] In the first cold rolling process, the second cold rolling process, and the final cold rolling process, a number of passes may be set to achieve a predetermined total rolling reduction ratio so that the plate is rolled to a desired thickness within an appropriate load range. Note that a pass refers to a single pass in which the plate is rolled between a pair of work rolls.

[0045] In the manufacturing method of the aluminum alloy sheet for can body, a finish annealing step may be performed after the cold rolling, if necessary. In the finish annealing step, the cold rolled sheet after the final cold rolling step is held at a predetermined finish annealing temperature for a predetermined time. The finish annealing temperature may be, for example, 100°C or more and 200°C or less. The time for holding the finish annealing temperature may be, for example, 2 hours or more and 4 hours or less. EXAMPLES

[0046] Although the embodiment of the present invention has been described above, examples in which the effects of the present invention have been confirmed will be specifically described below in comparison with comparative examples that do not satisfy the requirements of the present invention. Note that the present invention is not limited to these examples.

[0047] Manufacturing of aluminum alloy plate for can body Molten aluminum alloys (No. 1 to No. 8) with the compositions shown in Table 1 were poured into a mold to produce ingots with a thickness of 50 mm. The surface of the produced ingots was chamfered to a thickness of 45 mm. The ingots after chamfering were placed in an atmospheric furnace and heated from room temperature to 600°C at a heating rate of 40°C / hour, held at 600°C for 10 hours, then cooled to 500°C at a cooling rate of 10°C / hour, and then held at 500°C for 10 hours. Immediately after the holding period, hot rolling was started to produce hot-rolled plates with a thickness of 10 mm.

[0048] The hot-rolled sheet thus obtained was subjected to a first cold rolling process so as to have a sheet thickness of 2.7 mm (processing rate: 73%) to obtain a first cold-rolled sheet. The first cold-rolled sheet thus obtained was heated from room temperature to 270°C at a heating rate of 40°C / hour, held at 270°C for 4 hours, and then cooled to 200°C at a cooling rate of 40°C / hour, followed by air cooling.

[0049] Next, a secondary cold rolling process was carried out so that the plate thickness was 2.4 mm (processing rate: 11%) to obtain a secondary cold-rolled plate. The obtained secondary cold-rolled plate was heated from room temperature to 340°C at a heating rate of 40°C / hour, held at 340°C for 4 hours, cooled to 200°C at a cooling rate of 40°C / hour, and then air-cooled. Next, a final cold rolling process was carried out so that the plate thickness was 0.3 mm (processing rate: 87.5%) to obtain a cold-rolled plate. Thereafter, the cold-rolled plate was put into an atmospheric furnace heated to 150°C, held at 150°C for 3 hours, and a finish annealing process was carried out to produce an aluminum alloy plate for a can body having a plate thickness of 0.3 mm.

[0050] Nos. 1 to 5 correspond to examples, and Nos. 6 to 8 correspond to comparative examples.

[0051] [Table 1]

[0052] Post-baking strength Each aluminum alloy sheet produced was subjected to a heat treatment (baking treatment) at 200°C for 20 minutes. Tensile test pieces with a width and length halved based on the JIS No. 5 test piece specified in JIS Z 2241 (2011) were taken from the heat-treated sheets. The rolling direction was set as the longitudinal direction of the test pieces. A tensile test was performed using these test pieces to determine the 0.2% yield strength, which was taken as the post-baking yield strength. Test pieces with a post-baking yield strength of 200 MPa or more and 300 MPa or less were rated A (pass), and those with a post-baking yield strength of less than 200 MPa were rated B (fail). The results are shown in Table 2.

[0053] Number density of intermetallic compounds with a circle equivalent diameter of 0.10 μm or more and less than 1.00 μm A cross section parallel to the rolling direction of each of the prepared aluminum alloy sheets was filled with resin and polished to prepare a specimen for cross-sectional observation. COMPO images (composition images) were taken from 10 fields of view using a JEOL scanning electron microscope "JSM-7001F" at an accelerating voltage of 15 kV and a magnification of 5000 times. The obtained COMPO images were used to measure the area of ​​each Al-Fe-Mn or Al-Fe-Mn-Si intermetallic compound. The circle-equivalent diameter was calculated from the area of ​​each intermetallic compound, and the number of intermetallic compounds with a circle-equivalent diameter of 0.10 μm or more and less than 1.00 μm per unit area was calculated to obtain the number density. The number density of intermetallic compounds with a circle-equivalent diameter of 0.10 μm or more and less than 1.00 μm was 1.7 × 10 5 pieces / mm 2 Above 4.0×10 5 pieces / mm 2 The following is considered an A (pass), and the score is 1.7 x 10 5 pieces / mm 2 Less than or equal to 4.0 x 10 5 pieces / mm 2 Those that were over the limit were rated as B (failure). The results are shown in Table 2.

[0054] The number density of intermetallic compounds with a diameter equal to or larger than the critical circle equivalent diameter that act as nuclei for recrystallization For the intermetallic compounds having an equivalent circle diameter of 0.10 μm or more and less than 1.00 μm obtained by the method described above, the area fraction f and the average radius r of the intermetallic compounds were calculated. The area fraction f was calculated as the ratio of the total area of ​​the intermetallic compounds to the area of ​​the observation field. The average radius r was calculated as the arithmetic mean of the equivalent circle diameters of the intermetallic compounds. From the calculated area fraction f and average radius r of the intermetallic compounds, the critical equivalent circle diameter η of the intermetallic compounds that will become the nuclei of recrystallization was calculated using the following formula (see HE Vatne, O. Engler, E. Nes: Materials Science and Technology, February, 1997, Vol. 13, pp. 93-102.): PSN was calculated for each sample. η PSN =(4 / 3) / (10 6 -(3f / 2r))

[0055] Next, a cross section parallel to the rolling direction of each of the prepared aluminum alloy sheets was filled with resin and polished to prepare a specimen for cross-sectional observation. Using a JEOL scanning electron microscope "JSM-7001F," COMPO images (composition images) were taken from 20 fields of view at an accelerating voltage of 15 kV and a magnification of 500x. The obtained COMPO images were used to measure the area of ​​each Al-Fe-Mn or Al-Fe-Mn-Si intermetallic compound. The circle equivalent diameter was calculated from the area of ​​each intermetallic compound, and the previously obtained critical circle equivalent diameter η PSN The number of intermetallic compounds per unit area was calculated and used as the number density. This number density is 1.0×10 3 pieces / mm 2 More than 3.5 x 10 3 pieces / mm 2 Samples with a score of 1.0 x 10 or less were rated as A (pass). 3 pieces / mm 2 Less than or equal to 3.5 x 10 3 pieces / mm 2 The samples that exceeded the following were rated as B (failed). The results are shown in Table 2.

[0056] Circumferential anisotropy of the wall thickness at the opening of the drawn cup A blank with a diameter of 66.7 mm was punched out from the aluminum alloy sheet with a thickness of 0.3 mm, and the blank was drawn under a blank holding load of 3 kN to produce a drawn cup with a diameter of 40 mm (hereinafter, simply referred to as "cup") (drawing ratio 1.67). Using the produced cup, the wall thickness near the cup opening (position 17 mm high from the bottom) was measured at 22.5° intervals in the circumferential direction. That is, the rolling direction was set to 0°, and the wall thickness was measured in the 0° direction, 22.5° direction, 45° direction, 67.5° direction, 90° direction, 112.5° direction, 135° direction, 157.5° direction, 180° direction, 202.5° direction, 225° direction, 247.5° direction, 270° direction, 292.5° direction, 315° direction, and 337.5° direction. From the data of the 16 points obtained, the average thickness in the 0° direction and the 180° direction was calculated as the 0° average value; the average thickness in the 22.5° direction, the 157.5° direction, the 202.5° direction, and the 337.5° direction was calculated as the 22.5° average value; the average thickness in the 45° direction, the 135° direction, the 225° direction, and the 315° direction was calculated as the 45° average value; the average thickness in the 67.5° direction, the 112.5° direction, the 247.5° direction, and the 292.5° direction was calculated as the 67.5° average value; and the average thickness in the 90° direction and the 270° direction was calculated as the 90° average value. Furthermore, from these five numerical values, the maximum value (maximum thickness), the minimum value (minimum thickness), and the average value (average thickness) were calculated, and the circumferential anisotropy (%) was calculated from the following formula. Circumferential anisotropy = (maximum thickness - minimum thickness) / average thickness x 100 [%] Samples with circumferential anisotropy calculated from the above formula of 10.8% or less were rated A (pass), and samples with circumferential anisotropy exceeding 10.8% were rated B (fail). The results are shown in Table 2.

[0057] [Table 2]

[0058] As shown in Tables 1 and 2, the number density of intermetallic compounds having a Si content of 0.16 mass% or more and 0.60 mass% or less and a circle equivalent diameter of 0.10 μm or more and less than 1.00 μm is 1.7 × 105 pieces / mm 2 Above 4.0×10 5 pieces / mm 2 The number density of intermetallic compounds with a diameter equal to or larger than the critical circle equivalent diameter is 1.0×10 3 pieces / mm 2 More than 3.5 x 10 3 pieces / mm 2 The following Nos. 1 to 5 had small circumferential anisotropy and were excellent.

Claims

1. Si: 0.16 mass% or more and 0.60 mass% or less, Fe: 0.3 mass% or more and 0.6 mass% or less, Cu: 0.10 mass% or more and 0.35 mass% or less, Mn: 0.5 mass% or more and 1.2 mass% or less, Mg: 0.7 mass% or more and 2.0 mass% or less, and the remainder consists of Al and inevitable impurities, In the microstructure observation, the number density of intermetallic compounds having a circle equivalent diameter of 0.10 μm or more and less than 1.00 μm was 1.7 × 10 5 pieces / mm 2 Above 4.0 x 10 5 pieces / mm 2 is as follows: The number density of intermetallic compounds with a diameter equal to or larger than the critical circle equivalent diameter that becomes the nucleus of recrystallization is 1.0 × 10 3 pieces / mm 2 Above 3.5 x 10 3 pieces / mm 2 1. An aluminum alloy plate for can bodies, comprising:

2. Further comprising at least one component selected from the group consisting of Cr, Zn and Ti; 2. The aluminum alloy sheet for can bodies according to claim 1, wherein the contents of Cr, Zn and Ti are, respectively, Cr: 0.01% by mass or more and 0.10% by mass or less, Zn: 0.01% by mass or more and 0.40% by mass or less, and Ti: 0.005% by mass or more and 0.100% by mass or less.

3. Further comprising at least one component selected from the group consisting of Cr and Ti; The Cr and Ti contents are Cr: 0.01 mass% or more and 0.10 mass% or less, and Ti: 0.005 mass% or more and 0.100 mass% or less, respectively; 2. The aluminum alloy sheet for can bodies according to claim 1, wherein the total content of Cr and Ti is 0.01% by mass or more and 0.150% by mass or less.

Citation Information

Patent Citations

  • Aluminum alloy sheet excellent in high speed ironing formability for di can drum and manufacture therefor

    JP1998121177A

  • Production of aluminum base alloy sheet for deep drawing

    JP1998330896A

  • Method for manufacturing aluminum alloy sheet

    JP2006207006A

  • Aluminum alloy sheet for can body excellent in circularity of drawn cup, and method for producing the same

    JP2009235475A

  • Aluminum alloy sheet for drink can barrel, and method for producing the same

    JP2009235477A